Evaluación de la efectividad del ácido peracético como agente antimicrobiano en los talleres agroindustriales sección cárnicos de la ESPAM MFL - Barreto Rodríguez, Evelyn Virginia (2022)
Peracetic acid, also known as peroxyacetic acid, was used as an antimicrobial agent in the meat processing workshop facilities of ESPAM MFL, in order to evaluate its active cycle, when diluted in 20 L of water at room temperature each of its concentrations (200, 400, 600, 800 and 1000) ppm to be later applied in three different machines (cutter, mill and filler). In this investigation, the different solutions were compared against a control (quaternary ammonium) with a concentration of 500 ppm also, diluted in 20 L of water. The samples were microbiologically analyzed for mesophilic Aerobes, Staphylococcus aureus, Total Coliforms and Escherichia coli. The results express a greater efficacy of peracetic acid in all the microorganisms evaluated except for Mesophilic Aerobes, in addition, it was evidenced as the least effective treatment at T1 (200 ppm) and as the best treatment at T4 (800 ppm). On the other hand, according to the statistical analyzes carried out, the null hypothesis is accepted, so it is verified that none of the treatments has an effect on the microorganisms studied.